Refraction and correction in practice of optometrist - Sever, Anja (2017)
My hypothesis question is regarding “research” on methods which are evaluating the results for prescription in astigmatic values. The important issue for me, by delivered answers in the problem of clients, are how do clients understand the procedure itself, mostly the procedure JCC and within comparison with other method Clock Chart.